Sustainability Issues in Civil Engineering - Sivakumar Babu, G.L.; Saride, Sireesh; Basha, B. Munwar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This compilation on sustainability issues in civil engineering comprises contributions from international experts who have been working in the area of sustainability in civil engineering. Many of the contributions have been presented as keynote lectures at the International Conference on Sustainable Civil Infrastructure (ICSCI) held in Hyderabad, India. The book has been divided into core themes of Sustainable Transportation Systems, Sustainable Geosystems, Sustainable Environmental and Water Resources and Sustainable Structural Systems. Use of sustainability principles in engineering has become an important component of the process of design and in this context, design and analysis approaches in civil engineering are being reexamined to incorporate the principles of sustainable designs and construction in practice. Developing economies are on the threshold of rapid infrastructure growth and there is a need to compile the developments in various branches of civil engineering and highlight the issues. It is this need that prompted the composition of this book. The contents of this book will be useful to students, professionals, and researchers working on sustainability related problems in civil engineering. The book also provides a perspective on sustainability for practicing civil engineers who are not directly researching the problems but are affected by the concerns in the course of their profession. The book can also serve to highlight to policy makers and governing bodies the need to have a mandate for sustainable infrastructural development.
Part 1: Sustainable Transportation Systems -- Sustainable Usage of Construction and Demolition Materials in Roads and Footpaths -- A Few Dilemmas Pertaining Transportation Infrastructures and their Sustainability -- Bitumen Stabilized Materials for Sustainable Road Infrastructures -- Sustainable Transportation for Indian Cities: Role of Intelligent Transportation Systems -- Economic Sustainability Considerations in Asphalt Pavement Design -- Sustainable Design of Indian Rural Roads with Reclaimed Asphalt Materials -- Sustainability of Railway Tracks -- Use of System Approach To Identify, Evaluate and Implement Sustainable Policies and Practices in the Road Construction Industry -- Part 2: Sustainable Geosystems -- Resilient and Sustainable Geotechnical Solution: Lessons Learned from the 2011 Great East Japan Disaster -- Reinforced Piled Embankments for Sustainable Infrastructure Development -- Experimental Modeling of Unsaturated Intermediate Geomaterials for Sustainable Design of Geotechnical Infrastructure -- Underground Space for Sustainable Urban Development: Experiences from Urban Underground Metro Constructions in India -- Sand - Tire Chips Mixtures for Sustainable Geo-Engineering Applications -- Evaluation of Bioreactor Landfill As Sustainable Land Disposal Method -- <part 3:="" sustainable="" environmental="" and="" water="" resources -- Assessment of Landfill Sustainability -- Approaches To Selecting Sustainable Technologies for Remediation of Contaminated Sites: Case Studies -- Disinfection of Water using Pulsed Power Technique:Effect of System Parameters and Kinetic Study -- Part 4: Sustainable Structural Systems -- Pre-Engineered Bamboo Structures: A Step Towards Sustainable Construction -- Sustainability- way forward in Architectural Engineering -- Harnessing Sustainable Solutions through Challenges - A Case Study of World Record Long-Distance Pumping of Concrete.
Keywords: Civil engineering; Sustainability; Energy policy; Energy and state; Water; Hydrology; Civil Engineering; Sustainability; Energy Policy, Economics and Management; Water